If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 156 + -7x = 20x + 24 Reorder the terms: 156 + -7x = 24 + 20x Solving 156 + -7x = 24 + 20x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20x' to each side of the equation. 156 + -7x + -20x = 24 + 20x + -20x Combine like terms: -7x + -20x = -27x 156 + -27x = 24 + 20x + -20x Combine like terms: 20x + -20x = 0 156 + -27x = 24 + 0 156 + -27x = 24 Add '-156' to each side of the equation. 156 + -156 + -27x = 24 + -156 Combine like terms: 156 + -156 = 0 0 + -27x = 24 + -156 -27x = 24 + -156 Combine like terms: 24 + -156 = -132 -27x = -132 Divide each side by '-27'. x = 4.888888889 Simplifying x = 4.888888889
| X+3=(Y+3)*2 | | 6m^2-28m-48=0 | | -2(x-7)-140=5x-7(x+8) | | -n+6=-(n-8) | | X^3-x^2-4x+4=o | | X-3=3(Y-3) | | .10(y-4)+016y=.2y-2.8 | | 11-10x=79-24x | | 3x^2-26x+16=0 | | z-6=9z-6-z | | (x+5)(5x-4)=(x-4)(1-3x) | | x^5+17x=36 | | 10x-5=x^2+7x+5 | | 3y-3= | | 10y-6+4y=8y-90 | | 2y^2+3=21 | | 4x+9=-47-10 | | (x-8)(5x+6)=(x-10)(4x+3) | | 3y^2-2y-16=0 | | 106-4x=2x+16x | | x^2+2x-6=3x+12 | | 8u=-32 | | 171-3x=24x-24 | | 5u+14=59 | | x^2+2x-6=3x+y+12 | | 262=192-x | | 5(x+2)=-(x+14) | | 5-8x=50-43x | | (3)+(-7)+(11)=x | | 4u+5=-15 | | 0.4x+1.2=4.8 | | 0.3x+1.4(2x-5)=-22.5 |